Using virtual worlds as a platform for collaborative meetings in healthcare: a feasibility study - Michael J. Taylor; Chiya Shikaislami; Chris McNicholas; David Taylor; Julie Reed; Ivo Vlaev (BMC, 2020)
Abstract Background Healthcare teams often consist of geographically dispersed members. Virtual worlds can support immersive, high-quality, multimedia interaction between remote individuals; this study investigated use of virtual worlds to support remote healthcare quality improvement team meetings. Methods Twenty individuals (12 female, aged 25-67 [M = 42.3, SD = 11.8]) from 6 healthcare quality improvement teams conducted collaborative tasks in virtual world or face-to-face settings. Quality of collaborative task performances were measured and questionnaires and interviews were used to record participants' experiences of conducting the tasks and using the virtual world software. Results Quality of collaborative task outcomes was high in both face-to-face and virtual world settings. Participant interviews elicited advantages for using virtual worlds in healthcare settings, including the ability of the virtual environment to support tools that cannot be represented in equivalent face-to-face meetings, and the potential for virtual world settings to cause improvements in group-dynamics. Reported disadvantages for future virtual world use in healthcare included the difficulty that people with weaker computer skills may experience with using the software. Participants tended to feel absorbed in the collaborative task they conducted within the virtual world, but did not experience the virtual environment as being 'real'. Conclusions Virtual worlds can provide an effective platform for collaborative meetings in healthcare quality improvement, but provision of support to those with weaker computer skills should be ensured, as should the technical reliability of the virtual world being used. Future research could investigate use of virtual worlds in other healthcare settings.